A comparative analysis in the cognitive processing of information at the coaches age groups (Under 21 years old) football, according to the system of representation usually(Auditory, visual, sensory) - Reza, sabah; Abdul Hassan, Muhannad (Journal of Physical Education, 2011)
The Definition of research: introduction and included in the research and the importance of the fact that cognitive therapy is an important factor in the possibility and influential football coach, especially when combined with the identification of the system of representation usually has a knowledge of the differences according to the system The research problem lies in the lack of access to the coach to recognize the importance of the systems represent information and its importance in the handling of knowledge is better in order to achieve the full objectives of the training process as the goal of research is to identify differences in the cognitive processing of information at the coaches age groups (under 21 years old) football, according to the system of representation usually (auditory, visual, sensory). While the areas of research are the trainers of age groups (under 21 years) in Iraq for the period from 13 / k / 2 to 19 / k 2 / 2010 in the classrooms and playgrounds Faculty of Physical Education at the University of Baghdad School and Amu Baba age groups, while contains Part II on theoretical studies and studies of similar and sleep address for processing cognitive information and systems of representation the dominant means of collecting information in the NLP and then cognitive processing of information in the sports field with contains Section III on the approach used in the research, a descriptive approach in a manner study the comparative analysis, society and the research sample of coaches for the age groups, football has been used as researchers test Sonayat systems representative and testing knowledge of football and your training course for the Union in Part IV has been the results of test systems, analog and then the results of each system PHP variables of the study in question, where has been circles billing, standard deviations and the results of test analysis of variance single test less significant difference in the Title V concluded that researchers there are significant differences in the ability to cognitive processing of information at the coaches age groups (under the age of 21) football and according to the systems of representation dominant they have, and the high proportion of the audio system compared to the puppet regimes (sensory and visual) between the coaches age group football in Iraq and then have recommended to conduct similar studies on the age groups of trainers sporting events and other similar studies conducted on applicants coaches football and to conduct similar studies on systems with joint representation .